Platelet Behaviour in Non-Insulin-Dependent Diabetes -Influence of Vascular Complications, Treatment and Metabolic Control - Peacock, I; Hawkins, M; Heptinstall, S (Thrombosis and Haemostasis, 1986)
Platelet-rich plasma was prepared from 47 patients with noninsulin-dependent diabetes treated with glibenclamide and metformin, and 21 controls. The release of radio-labelled 5-hydroxy-tryptamine in response to aggregating agents (adenosine diphosphate, adrenaline and sodium arachidonate), and the effects on release of a selective thromboxane inhibitor (UK-34787) were investigated. Subsequently, 20 of the diabetic subjects were chosen at random for treatment with insulin; the remainder continued to take tablets. Platelet studies were then repeated, in all patients, after 4 and 6 months.The results showed an association between platelet behaviour and the presence of vascular complications, and were consistent with previous observations of reduced platelet reactivity in patients taking sulphonylureas. There was no correlation of platelet reactivity with blood glucose, glycosylated haemoglobin or lipid levels.
Keywords: Non-insulin-dependent diabetes mellitus; Platelet reactivity; Sulphonylureas; Vascular complications of diabetes